REFORMASI INFORMASI DALAM PELAYANAN BIROKRASI - Erasmus Nabit (to-ra, 2020)
In the law making theory (Law Making), there are three institutions that have authority in theformation of law, namely the legislative as an institution that forms laws; state administrativeinstitutions which are carried out daily by the Bureaucracy that forms administrative law; andcourt or judge decisions in concrete legal cases. This paper merely discusses bureaucracy as thespearhead of the state administration in conducting public services directly to the public. Suchbureaucracy is related to the needs of the community to obtain a variety of accurate informationneeded in the form of population data, labor, employment and others that are quickly andaccurately using information technology through internet access. As for the example is thecomparison of the role of the bureaucratic authority in managing Indonesian Population Data,namely the Central Statistics Agency (BPS) and the Australian Bureau of Statistics (ABS). Keywords: State Administrative Law, Bureaucracy, Public Services, Internet Access, AccurateInformation, and Discretion